Emission reduction in MSW management using composting - Beh, Shiau Hewi; Agamuthu, Pariatamby (2011)
Eighteen percent of global anthropogenic methane emission is contributed by waste sector. Today, landfilling is the most common municipal solid waste (MSW) management technology. Due to the worsening global warming, MSW management is switching to more environmental friendly options such as energy recovery from landfill gas and composting. This paper presents an estimation of emissions reduction from MSW management using composting compared to landfilling. MSW samples were taken from residential and commercial areas in Selayang and Rawang. The samples were then sorted into categories by material types. ‘Baseline’ is the scenario where the collected MSW was originally disposed off at the Bukit Tagar Sanitary Landfill. In order to prevent greenhouse gas (GHG) released into the atmosphere, a composting plant is proposed as an alternative to convert the organic materials into compost, which is the ‘project activity’. Emissions from baseline and project activity were calculated and compared based on methodology ASM III-F under Clean Development Mechanism (CDM), United Nation Framework Convention on Climate Change (UNFCCC). Differences in the emissions between baseline and project activity is taken as the emission reduction. Emissions from baseline and project activity will be 8,058.97 tCO2e and 132.18 tCO2e (for 10 years), respectively. Composting as an alternative will generate an emission reduction of 7,926.79 tCO2e, equivalent to 98% of methane being prevented.